The Influence of Pricing and Product Quality on Indihome Service Purchasing Decisions (Consumer Survey at PT Telkom Pekanbaru City) - Usman Usman; Endang Sutrisna; Mandataris Mandataris (Departement of Mathematics Education, 2022)
This study aims to determine the effect of pricing and product quality on the purchase decision of Indihome products at PT Telkom Pekanbaru City. The method used in this research is descriptive and quantitative statistics with explanatory research. The sample in this study amounted to 100 respondents who were determined using the purposive sampling technique and using a questionnaire for data collection techniques. From the data analysis which includes validity test, reliability test, linear regression analysis, hypothesis testing, and coefficient of determination test, the results show that pricing has a significant effect on purchasing decisions by t count (9,690) > t table (1,661), product quality has a significant effect on purchasing decisions of t count (8.075) > t table (1, )